Pengaruh Penambahan Ekstrak Bunga Telang (Clitoria ternatea Linn) Terhadap Karakteristik Marshmallow - Padmawati, I Gusti Ayu; Kartika Pratiwi, I Desak Putu; Sri Wiadnyani, Anak agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i01.p05, 2022)
This research was aimed to determine the effect of addition of blue butterfly pea extract on the characteristics of marshmallow and to determine the concentration of blue butterfly pea extract that produced the best characteristics of marshmallow. This research used completely randomized design with concentration of blue butterfly pea extract as treatments, which consisted of five levels: 0%, 0.3%, 0.6%, 0.9%, and 1.2%. The observed parameters include the physical, chemical, and sensory properties. The result showed that the five concentrations of blue butterfly pea extract had a significant effect on texture, color intensity, water content, anthocyanins, antioxidant activity, color (scoring and hedonic), flavor, texture, aroma, overall acceptance (hedonic) of the product. Selected product was marshmallow with the addition of 1.2% blue butterfly pea extract. The product has texture parameters of 1.28 N, color intensity L 16.71, a* 11.68, b* 7.62, 1.36% water, 1.48 mg/100 g anthocyanin, 43.50% antioxidant activity, blue color and liked, aroma, taste and overall acceptance were liked.